Active facilitation of focus groups: Exploring the implementation of inclusive education with research participants - Norma RA Romm; Norma M Nel; Lloyd DN Tlale (South African Journal of Education, 2013)
In this article, we explain how we took an "active" approach to focus group discussions with teachers in three South African schools. The topic of discussion was their views on the implementation of inclusive education. We shall also show how we sought feedback from the participants on their experiences of these discussions. In seeking this feedback, we were interested in seeing if they interpreted the sessions as being learning experiences - that is, as sessions that enabled the participants to learn from each other as well as from facilitators with a view to promoting mutual learning. We indicate how the participants chose to use the feedback opportunity to suggest that further processes should be put in place (by us) in the light of their expressed concerns. Finally, we outline how we took responsibility by creating a further forum for discussion with those who were regarded as having additional "actioning" power.